2009
DOI: 10.1074/jbc.m808199200
|View full text |Cite
|
Sign up to set email alerts
|

Critical Involvement of the Hinge Region of the Follicle-stimulating Hormone Receptor in the Activation of the Receptor

Abstract: The follicle-stimulating hormone receptor (FSHR) is a G-protein-coupled receptor with a large hormone-specific extracellular domain (amino acids (aa) 1-366) and a characteristic seventransmembrane domain (TMD; aa 367-695). The extracellular domain is composed of leucine-rich repeats (LRRs; aa 18 -259) connected to TMD by a hinge region (HinR; aa 260 -366), whose role in the hormone action is not clearly understood. We generated a novel polyclonal HinR antibody that specifically stimulates cAMP production by HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 45 publications
9
66
0
Order By: Relevance
“…7B, the WT basal activities of GpHRs in terms of hormone-independent cAMP production vary widely, with TSHR being the "noisiest" receptor followed by FSHR and LHR. Moreover, as reported previously, removal of ECD further increased cAMP production for both TSHR and FSHR (7,35). This high basal cAMP level in TSHR/FSHR TMD mutants decreased by the introduction of HinR in the HinTMD mutants, suggesting that HinRs act as a tethered inverse agonist to the TMD, direct evidence for their roles in maintaining the basal as well as hormone-independent receptor activation (7, 24).…”
Section: Figure 5 Effect Mini-tmd Antibodies On Hormone-receptor Intsupporting
confidence: 58%
See 2 more Smart Citations
“…7B, the WT basal activities of GpHRs in terms of hormone-independent cAMP production vary widely, with TSHR being the "noisiest" receptor followed by FSHR and LHR. Moreover, as reported previously, removal of ECD further increased cAMP production for both TSHR and FSHR (7,35). This high basal cAMP level in TSHR/FSHR TMD mutants decreased by the introduction of HinR in the HinTMD mutants, suggesting that HinRs act as a tethered inverse agonist to the TMD, direct evidence for their roles in maintaining the basal as well as hormone-independent receptor activation (7, 24).…”
Section: Figure 5 Effect Mini-tmd Antibodies On Hormone-receptor Intsupporting
confidence: 58%
“…TSHR/LHR/FSHR Wild Type and Mutant Constructs-Stable cell lines expressing WT TSHR, LHR, and FSHR were created in HEK293 background and characterized as described previously (7,24,25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies in general have proved to be excellent tools to map the ligand-receptor contact points and mechanism of receptor activation (38,45). Recently, it was shown that antibodies against Notch receptor EGF repeats inhibit ligand-receptor interactions and signal transduction (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…FSHR/S226A did not express at sufficient levels to permit evaluation. It has been reported that the hinge region of FSHR is important in receptor activation (60,61). Although structural information is lacking beyond residue Glu 259 in FSHR (30), it appears that the last two/three strands are much shorter with fewer hydrogen bonds stabilizing the parallel strands.…”
Section: Tablementioning
confidence: 99%